Control and Operation of a Hybrid Actuator for Maglev Applications - Rickwärtz Jan Philipp (Sciendo, 2021)
The hybrid actuator presented in this article is meant to enable stationary and slow dynamic levitation in Maglev applications. The term ‘hybrid’ refers to the design of the actuator, which is a combination of permanent magnets (PM) and electromagnets. This paper presents an analytically computable control algorithm for the said hybrid actuator. The theory of magnetic circuits is summarized shortly and used to derive a cascaded control loop consisting of an inner current controller and an outer air gap controller. Since the uncontrolled hybrid actuator is inherently unstable, the system has to be stabilized. By introducing a PID-controller into the air gap control loop, the unstable behaviour of the uncontrolled system is changed into the system behaviour of a damped harmonic oscillator. The advantage of this approach is that the computed controller parameters of the PID-controller can easily be adjusted, so the system behaviour of damping and eigenfrequency can be selected within a certain range. For the execution of the control algorithm, a microcontroller (MCU) is used and for precise air gap measurement, an eddy current sensor is installed. Finally, the behaviour of the current- and air gap controller is discussed for different measurement results and the adjustable system behaviour of the damped harmonic oscillator is presented.